Allelopathic effect of Leucaena leucocephala (Lam.) R. de Wit. and Hovenia dulcis Thunb. on Mimosa bimucronata DC. Kuntze and Peltophorum dubium (Spreng.) Taub. germination - Ribeiro, Vandjore Mattos (2019)
The aim of this study was to determine the allelopathic effect of aqueous extracts of leaves of Leucaena leucocephala (Lam.) R. de Wit. and Hovenia dulcis Thunb. on germination and early development of Mimosa bimucronata DC Kuntze and Peltophorum dubium (Spreng.) . Extracts were prepared in dilution of 2.5%; 5%; 7.5% and 10% (w/v) and compared to the control. Both extracts revealed allelopathic potential on seed germination and initial growth of M. bimucronata. No negative interference of extracts from the donor species was observed on the germination of P. dubium. However, seedlings subjected to L. leucocephala extract suffered interference in the initial development, resulting in the elongation of the radicle to be more sensitive to the effects of the extracts. Thus, the results showed that aqueous extracts of the leaves of L. leucocephala and H. dulcis have inhibitory properties on germination and early development of M. bimucronata, as well as and early development of P. dubium